146k views
0 votes
Pleaseeeee help asap!!

Pleaseeeee help asap!!-example-1
User Kavitha
by
5.0k points

2 Answers

5 votes

Answer:

(D)
((g)/(f))(x)=(x^(2)-6)/(3x+1), x{\\eq}-(1)/(3)

Explanation:

Given: f(x)=
3x+1 and g(x)=
x^(2)-6.

To find:
((g)/(f))(x)

Solution: Given that f(x)=
3x+1 and g(x)=
x^(2)-6, then applying the operations on the functions f(x) and g(x), we get


((g)/(f))(x)= (g(x))/(f(x)), f(x)≠0


((g)/(f))(x)=(x^(2)-6)/(3x+1)

Thus,
((g)/(f))(x)=(x^(2)-6)/(3x+1), x{\\eq}-(1)/(3)

Hence, option D is correct.

User Joly
by
5.0k points
2 votes
ANSWER


D. \: \: \frac{ {x}^(2) - 6}{3x + 1} \: ,x \\e - (1)/(3)



EXPLANATION

The given functions are;



f(x) = 3x + 1


and


g(x) = {x}^(2) - 6


We want to find


( (g)/(f) )(x)


Recall that,



( (g)/(f) )(x) = (g(x))/(f(x))


This implies that,


( (g)/(f) )(x) = \frac{ {x}^(2) - 6}{3x + 1}

The restriction on this function is that, the denominator must not be zero.


Thus


3x + 1 \\e0




\Rightarrow x \\e - (1)/(3)

User Alexey Popov
by
6.0k points